The Voluntary Disclosure Dilemma: Unraveling the Compliance-Evasion Causality in Tax Administration - Bahtiar, Mirza; Qadri, Resi Ariyasa (WIM Solusi Prima, 2024)
This research investigates the causality between taxpayer compliance and tax evasion behaviors, specifically within the context of participants in the Voluntary Disclosure Program (PPS) registered at the Small Tax Office of West Pontianak. The study delineates its population as taxpayers who, prior to their engagement in the PPS, had outstanding tax liabilities on income derived from business or employment activities. Utilizing the documentation method, secondary data were solicited from pertinent governmental bodies to facilitate the research. A linear regression model was employed to analyze the relationship between the variables under consideration. The findings underscore the impact of pre-PPS tax evasion activities on subsequent enhancements in taxpayer compliance, as evidenced by ransom payments. The study contributes to governmental authorities by offering valuable information regarding the patterns of tax evasion behavior among PPS participants, thereby informing policy and enforcement strategies.